PENINGKATAN KINERJA PEGAWAI MELALUI MOTIVASI KERJA DAN LINGKUNGAN KERJA DI DINAS SOSIAL KOTA SERANG - Nabila, Nova; Khaeruman, Khaeruman; Susanto, Budi (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to analyze the relationship between improving employee performance with work motivation and the work environment at the Serang City Social Service. This research uses quantitative methods with primary data collected through questionnaires as the main instrument. The sampling technique applied was saturated sampling, where all members of the population, totaling 54 respondents, were sampled. Data analysis was carried out using the SPSS version 25 application to test the hypothesis. The research results show that there is a significant positive influence, both partially and simultaneously, from work motivation and work environment on improving employee performance at the Serang City Social Service. These findings indicate that to improve employee performance, attention needs to be given to both aspects simultaneously, by increasing work motivation and creating a supportive work environment. This research provides important insights for management in designing strategies to improve employee performance in the social services environment